Distributed Hash Table Theory, Platforms and Applications - Zhang, Hao; Wen, Yonggang; Xie, Haiyong; Yu, Nenghai (SpringerBriefs in Computer Science, 2013)
This SpringerBrief summarizes the development of Distributed Hash Table in both academic and industrial fields. It covers the main theory, platforms and applications of this key part in distributed systems and applications, especially in large-scale distributed environments. The authors teach the principles of several popular DHT platforms that can solve practical problems such as load balance, multiple replicas, consistency and latency. They also propose DHT-based applications including multicast, anycast, distributed file systems, search, storage, content delivery network, file sharing and communication. These platforms and applications are used in both academic and commercials fields, making Distributed Hash Table a valuable resource for researchers and industry professionals.